2017
DOI: 10.1038/srep44565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pesticides on microbial communities in container aquatic habitats

Abstract: Container aquatic habitats support a specialized community of macroinvertebrates (e.g. mosquitoes) that feed on microbial communities associated with decaying organic matter. These aquatic habitats are often embedded within and around agricultural lands and are frequently exposed to pesticides. We used a microcosm approach to examine the single and combined effects of two herbicides (atrazine, glyphosate), and three insecticides (malathion, carbaryl, permethrin) on microbial communities of container aquatic ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 42 publications
3
76
0
2
Order By: Relevance
“…Analyzing the response of soil microorganisms to metals and flotation reagents, individually and as mixtures, can serve for a greater understanding of the associated pollution impacts and for their prediction and management. The majority of studies have focused on the application of different traditional techniques at the community level [27,28] which cannot provide enough information on the spectrum of taxa in the exposed microbial community [28]. Previous to the present study, a microcalorimetric-based analysis was conducted to analyze the individual and interactive effect chemicals used here on the soil microbial activity [29].…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the response of soil microorganisms to metals and flotation reagents, individually and as mixtures, can serve for a greater understanding of the associated pollution impacts and for their prediction and management. The majority of studies have focused on the application of different traditional techniques at the community level [27,28] which cannot provide enough information on the spectrum of taxa in the exposed microbial community [28]. Previous to the present study, a microcalorimetric-based analysis was conducted to analyze the individual and interactive effect chemicals used here on the soil microbial activity [29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, pesticides also can affect the stability of microbial communities. Previous studies confirmed that pesticides may adversely affect the structure, composition, and function of microbial communities . For fermentation foods, fermentation process is mainly mediated by microorganisms, while few studies have reported the effects of pesticide residues in raw materials on fermentation microorganisms and the quality of fermented foods.…”
Section: Introductionmentioning
confidence: 60%
“…Previous studies confirmed that pesticides may adversely affect the structure, composition, and function of microbial communities. [8][9][10][11][12] For fermentation foods, fermentation process is mainly mediated by microorganisms, while few studies have reported the effects of pesticide residues in raw materials on fermentation microorganisms and the quality of fermented foods. Markedly, when the pesticide residues of grapes were introduced into the fermentation process, the presence of exogenous substances may affect the fermentation microbe composition, and thereby affecting the quality of wine.…”
Section: Introductionmentioning
confidence: 99%
“…[3]: The values of X and S correspond, respectively, to the change in cell mass (x F -x 0 ) and compound (s 0 − s F ) concentrations.…”
Section: Experimental Data Analysismentioning
confidence: 99%
“…com.mx), Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, Av. Wilfrido Massieu s/n Zacatenco, Mexico City CP 07738, Mexico Abbreviations: 2,4-D, 2,4-dichlorophenoxyacetic acid; BM, basal medium; MSM, minimal salt medium diversity and altered the community structure of aquatic ecosystems [3]. In addition, it is known that the combination of pesticides could enhance their adverse effects on soil microbial communities [4] and that the biodegradation rate of some pesticides is affected by the presence of organic coformulants [5].…”
Section: Introductionmentioning
confidence: 99%